NEED ANALYSIS OF THE USE OF LOCAL CONTENT FOR DESCRIPTIVE TEXTS FOR GRADE VIII STUDENTS OF SMPN 3 KATINGAN KUALA - Kurniawan, Agus; Usadiati, Wahyuningsih; Misrita, Misrita (Program Studi Magister Pendidikan Bahasa Inggris, Program Pascasarjana, Universitas Palangka Raya, 2021)
Students read texts to improve their English reading skill. In this case, students really need English reading texts to help them comprehend the local content according to their environment. This study applied a descriptive-qualitative method and to collect the data questionnaire was distributed to the students of Grade VIII of SMPN 3 Katingan Kuala as the respondents. The obtained data were analyzed using percentage. The results of this study indicated that students really needed English reading text materials containing their interest and needs of the local content to improve their reading comprehension.